Communication Strategies of the Participants of English Meeting Clubs - Mahmud, PhD (Scopus ID: 56435695400), Prof. Murni (Makassar State University, 2024)
This paper explores the use of English language in one communicative situation, known as English meeting club. Generally, English club meetings are designed to practice students’ conversations in English, and therefore, speakers or participants are expected to use English in their communication. In this paper, conversations in English club meetings are explored to see the styles of communication used. The main objectives were to find out the styles of languages or expressions used in English meeting clubs. The paper was based on the descriptive qualitative studies conducted in one English club meeting in Makassar, South Sulawesi. Data collected by recording the process of discussion in three meetings and analyzed the transcribed recordings by using the technique of Discourse Analysis. Findings show some styles in using the language to communicate such as the use of unstructured language, the use of first language and code-switching, and the use of polite markers. It can be seen that formality and informality are found in the communication applied in English meeting clubs. Results of these findings are significant in the study of sociolinguistics, a study of language use in a particular society, as well as in the study of TEFL, teaching of English as a foreign language.